JOINT OPTIMIZATION OF CAPACITATED LOT-SIZING WITH LOST SALES AND NON-CYCLICAL PREVENTIVE MAINTENANCE - Guo, Yuhan; Hrouga, Mustapha; Liu, Jiayao; Afifi, Sohaib; Allaoui, Hamid; Zhang, Yu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Joint optimization of maintenance and lot-sizing-related operations offers significant benefits for businesses. This research studies the joint optimization of non-cyclical preventive maintenance and capacitated lot-sizing with lost sales. The objective is to determine the optimal lot size in each period, decide the optimal preventive maintenance for servicing machines over a planning horizon, and minimize the total cost related to service, operation, setup, production, inventory, and lost sales. An innovative framework is proposed to solve the problem, consisting of a novel mixed-integer linear programming formulation and an approximative production-planning algorithm combined with a multi-neighborhood descendent approach. Extensive experiments based on real-world data are conducted to verify the effectiveness of the proposed framework.